Surgical Non-Regenerative Treatments for Peri-Implantitis: a Systematic Review - Ausra Ramanauskaite; Povilas Daugela; Ricardo Faria e Almeida; Nikola Saulacic (Stilus Optimus, 2016)
Objectives: The purposes of the present study were 1) to systematically review the literature on the surgical non-regenerative treatments of peri-implantitis and 2) to determine a predictable therapeutic option for the clinical management of peri-implantitis lesions. Material and Methods: The study search was performed on primary database MEDLINE and EMBASE from 2005 until 2016. Sequential screenings at the title, abstract, and full-text levels were performed. Clinical human studies in the English language that had reported changes in probing depth (PD) and/or bleeding on probing (BOP) and/or radiologic marginal bone level changes after peri-implantitis surgical non-regenerative treatment at 6-month follow-up or longer were included accordingly PRISMA guidelines. Results: The first electronic and hand search resulted in 765 citations. From 16 full-text articles reviewed, 6 were included in this systematic review. Surgical non-regenerative methods were found to be efficient in reducing clinical parameters. BOP and PD values were significantly decreased following implantoplasty and systematic administration of antibacterials, but not after local application of chemical compounds or diode laser. Similarly, significant improvement in clinical and radiographic parameters was found only after implantoplasty compared with resective surgery alone. We found significant heterogeneity in study designs and treatments provided among the pooled studies. All of the studies revealed an unclear or high risk of bias. Conclusions: Surgical non-regenerative treatment of peri-implantitis was found to be effective to reduce the soft tissue inflammation and decrease probing depth. More randomized controlled clinical trials are needed to assess the efficacy of surgical non-regenerative therapy of peri-implantitis.